2011
DOI: 10.1007/s00422-012-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling habituation in rat EEG-evoked responses via a neural mass model with feedback

Abstract: Habituation is a generic property of the neural response to repeated stimuli. Its strength often increases as inter-stimuli relaxation periods decrease. We propose a simple, broadly applicable control structure that enables a neural mass model of the evoked EEG response to exhibit habituated behavior. A key motivation for this investigation is the ongoing effort to develop model-based reconstruction of multimodal functional neuroimaging data. The control structure proposed here is illustrated and validated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(66 reference statements)
0
3
0
Order By: Relevance
“… 9 Also see Makeig et al ., 2002 , 2004 ; Mazaheri and Jensen, 2010 ; Laxminarayan et al ., 2011 ; Qian and Di, 2011 ; Scheeringa et al , 2011 . …”
mentioning
confidence: 99%
“… 9 Also see Makeig et al ., 2002 , 2004 ; Mazaheri and Jensen, 2010 ; Laxminarayan et al ., 2011 ; Qian and Di, 2011 ; Scheeringa et al , 2011 . …”
mentioning
confidence: 99%
“…Neural mass models (NMMs) are often used as biological models for simulating EEG and LFP data [7][8][9][10][11][12][13][14] and for the modelbased analysis of EEG and LFP [15]. NMMs are constructed using neuron population activity.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have shown that it is possible to reproduce the whole spectrum of MEG/EEG oscillations, using appropriate values of model parameters within a physiological range (David & Friston, 2003;Robinson et al, 2001). In addition, these models have been used to test specific hypotheses about brain processes, for example, resonance phenomena (Spiegler et al, 2011), habituation (Laxminarayan et al, 2012), aging (Pons et al, 2010), focal attention (Suffczynski et al, 2001), and vision (Nguyen Trong, Bojak, & Knö sche, 2012). Pathological activity such as epilepsy can also be emulated.…”
Section: Applications Of Neural Mass Modelsmentioning
confidence: 99%